2007
DOI: 10.1084/jem.20071966
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel population of Langerin+ dendritic cells

Abstract: Langerhans cells (LCs) are antigen-presenting cells that reside in the epidermis of the skin and traffic to lymph nodes (LNs). The general role of these cells in skin immune responses is not clear because distinct models of LC depletion resulted in opposite conclusions about their role in contact hypersensitivity (CHS) responses. While comparing these models, we discovered a novel population of LCs that resides in the dermis and does not represent migrating epidermal LCs, as previously thought. Unlike epiderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
587
3
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 462 publications
(632 citation statements)
references
References 32 publications
33
587
3
9
Order By: Relevance
“…Initial studies with the Dutch and French Langerin-DTR-EGFP models demonstrated that DT treatment efficiently ablated LC in the epidermis, as well as LC and blood-derived CD8 1 Langerin lo DC in the CLN. Contrary to expectation it was observed that the reconstitution of Langerin 1 DC populations in CLN preceded the reconstitution of LC in the epidermis by a couple of weeks and reappeared with similar kinetics to the blood-derived CD8 1 Langerin lo DC [30,35]. This suggested that either LC were capable of homing to CLN without trafficking through the epidermis or that another Langerin 1 DC subset existed.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Initial studies with the Dutch and French Langerin-DTR-EGFP models demonstrated that DT treatment efficiently ablated LC in the epidermis, as well as LC and blood-derived CD8 1 Langerin lo DC in the CLN. Contrary to expectation it was observed that the reconstitution of Langerin 1 DC populations in CLN preceded the reconstitution of LC in the epidermis by a couple of weeks and reappeared with similar kinetics to the blood-derived CD8 1 Langerin lo DC [30,35]. This suggested that either LC were capable of homing to CLN without trafficking through the epidermis or that another Langerin 1 DC subset existed.…”
mentioning
confidence: 88%
“…It is likely that rather than intrinsic differences between the two mouse lines, differences in CHS experimental technique account for the different results. The choice of hapten does not seem to be critical since the Dutch mice also have reduced CHS to oxazalone [35]. Rather, it appears that the timing of DT administration can affect the outcome since French mice treated with DT only on day À1 develop diminished CHS responses similar to the Dutch mice [36,37].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases dermal DC may play the immunostimulatory role previously attributed to LC [10][11][12]. Recently, a distinct subset of dermal DC was identified in mouse that expresses langerin and this subset might be important for immunostimulation [13][14][15] although so far, little is known about their function and whether a similar subset exists in humans. LC probably play a pivotal role in certain virus infections.…”
Section: Biology Of Lc and Interactions With Virusesmentioning
confidence: 99%
“…Par ailleurs, les travaux de Ginhoux et al [6] ont montré que les DDC langérine + avaient la capacité de capturer des antigènes exprimés au niveau cutané et de les véhiculer au niveau des ganglions lymphatiques cutanés. En complément de ces études, les travaux de Bursch et al, [7] ont montré que les DDC langérine + étaient à elles seules capables de contribuer au développement de réactions d'hypersensibilité de contact.…”
Section: Peau Ganglions Lymphatiques Cutanés Et Cellules Dendritiquesunclassified